2022
DOI: 10.1177/21925682221090926
|View full text |Cite
|
Sign up to set email alerts
|

Is Final Fusion Necessary for Growing-Rod Graduates: A Systematic Review and Meta-Analysis

Abstract: Study Design Systematic review and meta-analysis. Objectives The need for definitive fusion for growing rod graduates is a controversial topic in the management of Early-onset scoliosis (EOS) patients. The authors performed a systematic review and meta-analysis on the available literature to evaluate the outcomes of growing rod graduates undergoing final fusion or observation with implants in-situ. Methods An extensive literature search was carried out aimed at identifying articles reporting outcomes in growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…Our results support the conclusion of a recent systematic review of the literature, 35 which revealed a higher risk of complications in patients who underwent definitive fusion, further arguing for the solidity of mini-invasive constructs and against the need for posterior fusion. In their review, Ahuja and colleagues showed no differences regarding curve correction between fused and unfused patients, which is in line with our own results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results support the conclusion of a recent systematic review of the literature, 35 which revealed a higher risk of complications in patients who underwent definitive fusion, further arguing for the solidity of mini-invasive constructs and against the need for posterior fusion. In their review, Ahuja and colleagues showed no differences regarding curve correction between fused and unfused patients, which is in line with our own results.…”
Section: Discussionsupporting
confidence: 90%
“…The BFC allowing further growth of the spine is therefore indicated in immature patients, as confirmed by our own study, allowing early removal of bracing, which has been demonstrated to have a negative impact on the quality of life and treatment satisfaction while not avoiding curve progression 36,37 . Furthermore, the solidity of the BFC makes final spinal fusion unnecessary, preventing further surgical interventions in skeletally mature patients, as demonstrated by long-term studies and recent meta-analyses 17,33,35 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…After sTGR implantation, there was no significant difference in the major curve or the MK correction rate between the groups. The maximum correction of spinal deformity has been reported to occur during the initial implantation of a TGR (16). After that, the spinal malalignment fluctuates with the lengthening, and the final fusion can only obtain a modest correction due to autofusion and spinal rigidity caused by distractions (17).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the safety and feasibility of growing fusion rods for EOS, the surgical treatment causes significant pain, trauma, and psychological stress in pediatric patients [7][8]. In addition, a series of complications after surgery, such as bleeding, infection, and nerve function impairment, can lead to prolonged recovery time [9][10]. The challenges of postoperative care for PSF surgery are reducing patient pain and complications from analgesic medications and facilitating recovery from physical trauma.…”
Section: Introductionmentioning
confidence: 99%